South Africa Limpopo Basin Climate Change Adaptation Dataset - Ringler, Claudia; Sun, Yan (International Food Policy Research Institute, 2010)
This household survey was conducted as part of a project aimed to provide policymakers and stakeholders in South Africa with tools to better understand, analyze, and form policy decisions to adapt to global change. The survey was conducted in the Limpopo River Basin in South Africa during 2005. A total of 794 households from 19 districts, in 5 Water Management Areas (WMAs), across 4 provinces of South Africa were sampled. The South Africa sample was designed to capture the diverse agricultural patterns in the basin area: farming strata, type of cultivation (dry land and irrigation), major and minor crops and livestock, and all the sub-catchment areas in each of the 5 WMAs. Topics covered include household roaster including background information, farm and non-farm activities, assets, basic services, disease, shocks; land ownership and land holdings; farm machinery, farm buildings, wells and pumps, and wage rates; crop production including production cost and income for seasonal crops and for perennial crops; crop water use; livestock production; access to extension, markets and credit; expenditures on food and income; and climate change and adaptation options.